Ethical language and decision-making for prenatally diagnosed lethal malformations - Wilkinson, D; De Crespigny, L; Xafis, V (Elsevier, 2014)
In clinical practice, and in the medical literature, severe congenital malformations such as trisomy 18, anencephaly, and renal agenesis are frequently referred to as ‘lethal’ or as ‘incompatible with life’. However, there is no agreement about a definition of lethal malformations, nor which conditions should be included in this category. Review of outcomes for malformations commonly designated ‘lethal’ reveals that prolonged survival is possible, even if rare. This article analyses the concept of lethal malformations and compares it to the problematic concept of ‘futility’. We recommend avoiding the term ‘lethal’ and suggest that counseling should focus on salient prognostic features instead. For conditions with a high chance of early death or profound impairment in survivors despite treatment, perinatal and neonatal palliative care would be ethical. However, active obstetric and neonatal management, if desired, may also sometimes be appropriate.